Implementasi Etika Administrasi Negara Sebagai Upaya Untuk Mencegah Korupsi - Ni Made Sumerti Asih (Jurnal Ilmiah Raad Kertha, 2018)
State apparatus in realizing good governance is required to have more ethical obligation in relation to behavior compared with private person. Each State officer must have behavior which has superior character, nobility and various ethical principles which are based on moral virtue that is justice . The State Apparatus must genuinely understand and implement as much ethical values as possible in exercising his power and authority and in his official acts as a servant of society, nation and State. Corruption is an immoral act involving misuse of office, misappropriation of power in office, placement of persons or classes within the official office of power. It is a violation of societal norms, ethical norms and legal norms.Implementation of State Administration Ethics as an effort to prevent corruption is done by instituting ethical values in the Code of Ethics as well as legislation to be obeyed and implemented as a work ethic for State administrators. The Ethics of State Administration has been set forth, among others: in the Code of Conduct of the Corps of the Republic of Indonesia, Overseas Pledge Pledge, Civil Service Personnel Act No. 43 of 1999 and Government Regulation No. 53 of 2010. The Administration of the State is a Preventive Effort to Prevent Corruption